Impulse Control Difficulties and Hostility Toward Women as Predictors of Relationship Violence Perpetration in an Undergraduate Male Sample - Gildner, Daniel J. (Journal of interpersonal violence, 2021)
Relationship violence in college students continues to be an important social problem. Prior research has identified several risk factors for relationship violence including trauma exposure, impulse control difficulties, and hostility toward women; however, previous research assessing these variables has mainly focused on bivariate relationships, with little work attempting to connect multiple correlates to relationship violence while utilizing a theoretical, interactive approach. The purpose of this study was to simultaneously examine several correlates of relationship violence (i.e., hostility toward women, trauma exposure, and impulse control difficulties), and to examine male perpetration of relationship violence among a sample of male college students using a cross-sectional design. It was hypothesized that among men in this sample, hostility toward women and trauma exposure would moderate the relationship between impulse control difficulties and relationship violence. The findings suggested that college-aged men, who have high impulse control difficulties, high hostility toward women, and who have multiple trauma exposures, may be more likely to perpetrate relationship violence against a female intimate partner than those who are low in impulse control difficulties, report low levels of hostility toward women, or report fewer or no trauma exposures. Thus, the current study suggests that exposure to trauma predisposes men with specific attributes to relationship violence, which may provide a treatment target for future intervention programs.